Youth transitions - Skills, work and family formation: Preliminary findings from the round 5 survey in India - Lives, Y (Young Lives, 2017)
This fact sheet presents findings from the fifth round of the Young Lives survey of children in United Andhra Pradesh in 2016. Young Lives has followed two cohorts of children since 2002, most recently focusing on our Older Cohort (22-year-olds in 2016) to explore issues related to education, digital skills, transitions to the labour market, and on marriage and fertility. Given that a large and growing segment of India’s population is under 25 years, attainment of education and skills development are critical to ensuring that this turns into a demographic dividend not a liability. What these findings reveal is a young generation experiencing more education, but that poorer socio-economic groups are still leaving education sooner, and are more likely to be in work rather than any form of study, than more advantaged groups. Young women remain very much more likely to be married than young men, with many still marrying below the legal age. Gender and socio-economic divides are evident in access to the new technologies that are increasingly important to 21st century opportunities.